Reliability of using a pressure sensor system to measure in-water force in young competitive swimmers - Santos, Catarina C.; Marinho, Daniel A.; Costa, Mário J. (Frontiers in Bioengineering and Biotechnology, 2022)
The aim of this study was to analyze the reliability of using a differential pressure system to measure in-water force in young competitive swimmers. Ten boys and five girls (12.38 ± 0.48 years, 49.13 ± 6.82 kg, 159.71 ± 7.99 cm) were randomly assigned to perform two maximum bouts of 25 m front crawl on different days (trial one, T1; trial two, T2), one week apart. A differential pressure system composed of two hand sensors (Aquanex System, v.4.1, Model DU2, Type A, Swimming Technology Research, Richmond, VA, United States) was used to measure the peak (RFPEAK) and the mean (RFMEAN) resultant force of the dominant and non-dominant hands (in Newton, N). Reliability was analyzed by computing the intraclass correlation coefficient (ICC), typical error (TE), smallest worthwhile change (SWC), coefficient of variation (CV%), standard error of measurement (SEM), and the minimal detectable change (MDC). Bland–Altman plots with 95% limits of agreement were also analyzed. The results showed no differences between T1 and T2 in all variables (p > 0.05). The ICC showed “excellent” reliability (ICC > 0.90) for the RFPEAK and RFMEAN in both hands. The CV% was rated as “good” (<5%) and TE was smaller than SWC in all variables. The Bland-Altman plots showed high reliability with a small bias (RFPEAK dominant, -0.29 N; RFPEAK non-dominant, -0.83 N; RFMEAN dominant, 0.03 N; RFMEAN non-dominant, 0.50 N). The pressure sensor system (Aquanex System) seems to be a reliable device for measuring the hand resultant force during front crawl in young swimmers and can be used to monitor the changes over time.